CO2 methanation on Co/TiO2 catalyst: Effects of Y on the support. (31st December 2019) - Qin, Zuzeng; Wang, Xiaodi; Dong, Lihui; Su, Tongming; Li, Bin; Zhou, Yuwen; Jiang, Yuexiu; Luo, Xuan; Ji, Hongbing
Highlights: The doped Y enhanced the adsorption capacity of the CO2 . More Co3 O4 can be reduced into Co on the Y doped Co/TiO2 samples. Y could affect the TiO2 pores and increased the catalysts specific surface area. Y doped to TiO2 framework and formed oxygen vacancies and promoted CO2 activation. Abstract: The Y was used for improving the structural performance of TiO2 support. The results showed that the BET surface area was increased by doping Y, and more oxygen vacancies were generated in the TiO2 support, which would promote the activation of CO2 . The reduction temperature of the Co3 O4 was decreased and more Co3 O4 can be reduced into Co for the Y doped Co/TiO2 samples compared to that of the Co/TiO2 . Furthermore, the doped Y enhanced the basicity of the catalysts and the adsorption capacity of the CO2 was greatly increased, which was beneficial to the activation of the CO2 and the CO2 methanation reaction. The activity test indicated that the CO2 conversion and CH4 selectivity was highest when using the 20% Co/2%Y-TiO2 catalyst. The 20% Co/2%Y-TiO2 catalyst exhibited the highest CO2 conversion of 85.9%, and CH4 selectivity of 99.5% at 350 °C, and kept stable in 40 h.